Spanish adaptation and validation of the UGEQ questionnaire to assess group cohesion in university students - Ruiz-Robledillo, Nicolás (2023)
Introduction: The assessment of group cohesion is a fundamental aspect in the context of higher education. However, there is a need for appropriate and specific instruments to assess this construct in the university context. Objective: To adapt and validate the University Group Environment Questionnaire (UGEQ) group cohesion measure to the Spanish population. Method: The sample used for this study consisted of 309 Spanish university students, with a mean age of 22.61 (SD=5.5). For data analysis, a confirmatory factorial analysis was performed, following the structure of the original instrument (UGEQ). Results: The results suggest optimal adjustment indices (CFI= 0.92; TLI=0.90; SRMR=0.068 and RMSEA= 0.081 [90% CI: 0.071- 0.092]) and appropriate internal consistency (0.88 [95% CI: 0.86-0.90]) and temporal stability. Discussion: These findings support the use of the UGEQ as a valid and reliable instrument to assess group cohesion in the Spanish university context.